OR, PROSPÉRITÉ ET PAUVRETÉ A L’ÉPOQUE DE GLOBALISATION : RECHERCHES SUR UN PROJET MINEUR EN ROUMANIE POST-COMMUNISTE (2002-2011) - Mihai Pascaru (European Scientific Journal, ESJ, 2013)
This study summarizes a series of researches conducted by the author, under his direct coordination or substantial collaboration in the impact zone of Rosia Montana Gold Corporation mining project (RMGC), considered an important vector of globalization in Romania. After a brief presentation of the conceptual framework which links globalization to localization and after a short summary of the local context, including the RMGC project, the series of research shows a package of important issues such as: 1) RMGC’s psychosocial impact, 2) people’s representations of various project alternatives, 3) the subjective dimensions of the quality of life 4) comparative representation of traditional and modern mining, given that we want the project to bring a new dimension to modern gold mining. The conclusion of the study is a provisional one (open to other research). It also emphasizes that local effects of globalization are not mono-linear, but more complex and at least bi-directional: from global to local (RMGC’s project implementation efforts) and from local to global (delay of implementation and the potential of a deep localized implementation).